DISTRIBUTION PATTERN OF UNDERWATER ILLUMINANCE FOR SQUID NET FISHERIES IN MALAYSIA - Sakri Ibrahim; Mohd. Azrmi Ambak; Khalid Sarno; Mohamad Zaidi Zakaria; Zainal Ashirin Shahardin; Sukree Hajisamae (Research Center for Fisheries, 1998)
A study oIr the distribution pattern of underwater illuminance for squid net fisheries inMalaysiu rvas condueted fronr April to Septenrber, 1996 in sheltered waters of Kapas Island off the coast of Terengganu.